168k views
5 votes
Multiply (Assume all expressions appearing under a square root symbol represent nonnegative numbers)(√5 - 3)² =

Multiply (Assume all expressions appearing under a square root symbol represent nonnegative-example-1
User Vdebergue
by
5.9k points

1 Answer

3 votes

Given:


(√(y)\text{ -3\rparen}^2

Required:

Multiply (Assume all expressions appearing under a square root symbol represent nonnegative numbers)

Step-by-step explanation:


\mathrm{Simplify}\:\left(√(y)-3\right)^2

Apply perfect square formula we get


\left(a-b\right)^2=a^2-2ab+b^2

we place the value in this formula we get,


\begin{gathered} =(√(y))^2+(3)^2-2.√(y).3 \\ \\ ==\left(√(y)\right)^2-2√(y)\cdot\:3+3^2 \end{gathered}
\begin{gathered} (√(y))^2=y \\ \\ -2√(y)\cdot\:3=-6√(y) \\ \\ 3^2=9 \end{gathered}
=y-6√(y)+9

Required answer:


=y-6√(y)+9

User Rxw
by
5.7k points